2020
DOI: 10.1101/2020.03.22.997809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of biodiversity in estuaries using environmental DNA metabarcoding

Abstract: Biodiversity is an important parameter for the evaluation of the extant environmental conditions. Here, we used environmental DNA (eDNA) metabarcoding to investigate fish biodiversity in five different estuaries in Japan. Water samples for eDNA were collected from river mouths and adjacent coastal areas of two estuaries with high degrees of development (the Tama and Miya Rivers) and three estuaries with relatively low degrees of development (the Aka, Takatsu, and Sendai Rivers). A total of 182 fish species acr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…This is supported by the timing of our sampling during high tide, when the ocean level reaches its maximum and seawater freely enters the estuary. 22 demonstrated that species from the surrounding marine and freshwater habitats are more easily detected during this period.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This is supported by the timing of our sampling during high tide, when the ocean level reaches its maximum and seawater freely enters the estuary. 22 demonstrated that species from the surrounding marine and freshwater habitats are more easily detected during this period.…”
Section: Discussionmentioning
confidence: 88%
“…Our ndings agree with 16 who likewise found the greatest abundance of sh species in the midstream of the Merbok Estuary. This is an indicator that optimal conditions to support high biodiversity warrants a pristine environment 22 . The NMDS ordination allied with PERMANOVA based on read counts of the two metabarcoding assays, con rming clustering results that three distinct sh communities were distinguishable by the designated zones.…”
Section: Diversity Patterns and Compositionmentioning
confidence: 99%
“…Despite their importance, estuarine ecosystems are susceptible to anthropogenic effects and are suffering from severe alterations, degradation, or losses (Wingard and Lorenz 2014). In light of this critical situation in estuarine ecosystems, three papers on biodiversity monitoring using the MiFish metabarcoding methods from East Asian countries have been consecutively published in the past 6 months (Zhang et al 2019;Zou et al 2020;Ahn et al 2020).…”
Section: Estuarine Fish Communitymentioning
confidence: 99%
“…More recently, Ahn et al (2020) conducted biodiversity monitoring using MiFish eDNA metabarcoding at five estuaries with a broader geographic scale along the Japanese archipelago. Water samples were collected from river mouths and adjacent coastal areas of two and three estuaries with high and low degrees of development, respectively (Ahn et al 2020). A total of 182 fish species across 67 families were detected, 11 of which occurred in all of the rivers.…”
Section: Estuarine Fish Communitymentioning
confidence: 99%
See 1 more Smart Citation